2017
DOI: 10.1093/humupd/dmx021
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of male infertility: an analysis of the evidence to support the development of global WHO guidance—challenges and future research opportunities

Abstract: BACKGROUNDHerein, we describe the consensus guideline methodology, summarize the evidence-based recommendations we provided to the World Health Organization (WHO) for their consideration in the development of global guidance and present a narrative review of the diagnosis of male infertility as related to the eight prioritized (problem or population (P), intervention (I), comparison (C) and outcome(s) (O) (PICO)) questions. Additionally, we discuss the challenges and research gaps identified during the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
256
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(275 citation statements)
references
References 142 publications
(201 reference statements)
1
256
0
18
Order By: Relevance
“…The recommendations for genetic testing during the diagnostic work-up of male infertility have only minimally changed over the last 20 years and most of these recommendations still focus on the well-known and common causes of male infertility that were already known in the 1990’s (Barratt et al 2017; Jungwirth 2018). For cost-efficiency, there are guidelines to help stratify patient groups to receive pre-conceptive genetic tests such as karyotype analysis, AZF deletion tests or a screening for pathogenic variants in a single gene involved in a specific phenotype such as CBAVD or Kallmann syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recommendations for genetic testing during the diagnostic work-up of male infertility have only minimally changed over the last 20 years and most of these recommendations still focus on the well-known and common causes of male infertility that were already known in the 1990’s (Barratt et al 2017; Jungwirth 2018). For cost-efficiency, there are guidelines to help stratify patient groups to receive pre-conceptive genetic tests such as karyotype analysis, AZF deletion tests or a screening for pathogenic variants in a single gene involved in a specific phenotype such as CBAVD or Kallmann syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…For cost-efficiency, there are guidelines to help stratify patient groups to receive pre-conceptive genetic tests such as karyotype analysis, AZF deletion tests or a screening for pathogenic variants in a single gene involved in a specific phenotype such as CBAVD or Kallmann syndrome. A recent World Health Organization study on the diagnosis on male infertility suggested to at least perform karyotyping and AZF deletion tests in men with non-obstructive azoospermia or extreme oligoasthenoteratozoospermia (OAT) without a history of a known cause of spermatogenic failure such as chemotherapy, varicocele, orchitis or bilateral cryptorchidism (Barratt et al 2017). However, after stratification, in approximately 40% of all male infertility patients no genetic cause is found with the above mentioned tests (Krausz and Riera-Escamilla 2018) and this strongly suggests that much more genetic research is required and at the same time the use of other diagnostic assays should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Idiopathic oligoathenoteratozoospermia (iOAT) is a common finding in the evaluation of male infertility and is defined as a reduced spermatogenesis of unknown aetiology consisting of oligozoospermia (< 39 × 10 6 spermatozoa/ejaculate), asthenozoospermia (< 32% progressive motile spermatozoa) and teratozoospermia (< 4% normal forms) [1][2][3]. In the last years, the oestrogen antagonist, tamoxifen, has been suggested as an empiric (off-label) treatment option for iOAT [4].…”
Section: Efficacy Of the Oestrogen Antagonist Tamoxifen On Sperm Paramentioning
confidence: 99%
“…Though some potential sperm-specific contraceptive drug targets have been identified (Lishko and Mannowetz, 2018), our relatively poor understanding of the spermatozoon makes target-agnostic strategies more attractive (Barratt et al , 2017). Phenotypic drug discovery is undergoing a renaissance in a number of therapeutic areas because it can uncover novel biology in an unbiased way.…”
Section: Introductionmentioning
confidence: 99%